A note on a single-machine lot scheduling problem with indivisible orders. (March 2017) - Yang, Dar-Li; Hou, Yung-Tsung; Kuo, Wen-Hung
Abstract: In this paper, a lot scheduling problem on a single machine with indivisible orders is studied. The objective is to minimize the total completion time of all orders. We show that the problem is NP-hard in the strong sense. Then, a binary integer programming approach and four simple heuristics are proposed to solve the problem. The binary integer programming approach with running time limit is considered as one heuristic method. As compared to a lower bound, the average performances of the heuristic method are really good and better than those of the four simple heuristics. Highlights: A lot scheduling problem on a single machine with indivisible orders is studied. The objective is to minimize the total completion time of all orders. We show that the problem is NP-hard in the strong sense. A binary integer programming approach with run time limit is proposed. As compared to a lower bound, the average performance of the method good.